2011
DOI: 10.1057/jgm.2010.35
|View full text |Cite
|
Sign up to set email alerts
|

Similar biological medicinal products: lessons learned and challenges ahead

Abstract: In the European Union (EU) the concept of ' Similar biological (biosimilar) medicinal products ' has been introduced and accurately defi ned in the legislation in June 2003 (Directive 2003 / 63 / EC 1 and later modifi ed by Directive 2004 / 27 / EC 2 ). This provision allows the submission of a marketing authorization application (MAA) for a biological medicinal product by an

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 12 publications
0
3
0
1
Order By: Relevance
“…Regulations in France, Germany, and Spain do not allow the automatic substitution of biologicals, by 2011 [36]. Because they are different medicines, substitution between biosimilars should not occur [37].…”
Section: Interchangeability and Substitution In European Countriesmentioning
confidence: 99%
“…Regulations in France, Germany, and Spain do not allow the automatic substitution of biologicals, by 2011 [36]. Because they are different medicines, substitution between biosimilars should not occur [37].…”
Section: Interchangeability and Substitution In European Countriesmentioning
confidence: 99%
“…Aunque los BS están comercializados desde el año 2006, la introducción de los mismos ha sido baja 25 . En este ámbito existe un amplio debate en la literatura médica sobre los riesgos y beneficios de los BS, que ha aumentado con el desarrollo de BS de mAb [26][27][28][29][30][31][32][33][34][35] . En particular, hay distintos aspectos que han centrado el debate, como son: la complejidad estructural de los fármacos biológicos, la seguridad, la inmunogenicidad, la extrapolación de indicaciones, la intercambiabilidad, la sustitución y prescripción por denominación común internacional (DCI o INN) o por marca comercial.…”
Section: Controversias Sobre Biosimilaresunclassified
“…First, it is widely accepted that production costs for biological medicines are higher than for chemically derived molecules. In principle, this also holds for differences in the production costs of biosimilars and of generics [ 2 – 8 ]. A possible consequence of these higher costs is that ultimately fewer firms will produce biosimilars.…”
Section: Can Biosimilar Competition Resemble Generic Competition?mentioning
confidence: 99%
“…Consequently, there is a lack of independent analyses of the current and future savings from the use of biosimilars. Several authors reported estimates from the EGA where savings could attain up to €1.6 billion conditional on a 20 % price reduction for five patent-expired biologicals [ 3 , 5 , 8 , 22 ]. This rough estimate does not provide information based on the currently available biosimilars but ratter based on expectation of their apparition.…”
Section: What Savings Can Be Attributed To the Introduction Of Biosimmentioning
confidence: 99%